Plural ecologies in Southeast Asia: hierarchies, conflicts, and coexistence - Duile, Timo; Großmann, Kristina; Haug, Michaela; Sprenger, Guido (Routledge, 2023)
Plural Ecologies: Beyond ontology and political ecology in Southeast Asia / Guido Sprenger, Michaela Haug, Kristina Grossmann, Timo Duile -- Ontologies of possibility: Future-oriented indeterminacy in Southeast Asian animism / Guido Sprenger -- Conflicting ways of dealing with invisible human-like beings: Including -- Neglecting -- Ignoring / Susanne Rodemeier -- Home of spirits and loggers: Plural perspectives on the forest in Indonesian Borneo / Michaela Haug -- Animism and indigenous movements in Indonesia / Timo Duile -- Negotiating plural ecologies of adat land in Indonesia / Kristina Grossmann -- Ecological disturbances: Negotiating indigeneity and access to land in Indonesia / Birgit Bräuchler -- Entrepreneurial ecologies in a Javanese fishery / Katharina Schneider -- The reinvention of moral ecologies in Indonesia / Thomas Reuter -- "Talking" trees: Urban ecologies in late socialist Hanoi / Gertrud Hüwelmeier -- A positive other? Comprehending the hope in animism's overcoming the capitalist socio-ecological crisis / Michael Kleinod.
Keywords: Aufsatzsammlung; Nachhaltigkeit; Humanökologie; Südostasien